2022
DOI: 10.1038/s41598-022-17173-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dielectric properties in low-loss polypropylene-based composites at GHz frequencies: theory and experiment

Abstract: Polymer composites with high dielectric constant and low loss tangent are highly regarded as substrates for modern high-speed electronics. In this work, we analyze the high-frequency dielectric properties of two types of composites based on polypropylene infused with high-dielectric-constant microparticles. Two types of fillers are used: commercial ceramics or titanium oxide (TiO2) with different concentrations. The key observation is that adding the fillers causes an increase of dielectric constants by around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…26 They reported that the composite law is valid for the dielectric constant but not for the dielectric loss in certain cases. 27 A comparison was made with 10 and 30 wt % additions for the other fillers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 They reported that the composite law is valid for the dielectric constant but not for the dielectric loss in certain cases. 27 A comparison was made with 10 and 30 wt % additions for the other fillers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The dielectric constant and dielectric loss of alpha alumina at 18 GHz were 8.5 and 3 × 10 –3 , respectively, according to the split-spot measurement . They reported that the composite law is valid for the dielectric constant but not for the dielectric loss in certain cases . A comparison was made with 10 and 30 wt % additions for the other fillers.…”
Section: Resultsmentioning
confidence: 99%